(untitled) (Journal of Legal Studies, 2024)
This article tackles the sensible and complex problem of international taxation. The main objective of the paper is to create a comprehensive fiscal space, especially at the European level, in the direct taxation domain. The main scope of the research is to identify, evaluate, and assess the main pillars and features of this fiscal space. The research methodology is based both on theoretical analysis of double taxation and transfer pricing issues, but also on practical aspects of several specific case laws. The conclusions of the article highlight the further improvement and development of the arm’s length principle structure, improving double taxation multilateral conventions, recalibrating the mutual agreement procedure, and strengthening the tax authorities’ international cooperation techniques and tactics.